(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this study is to make an attempt to explore the problems and difficulties that areassociated with cyber crime in India from an ethical point of view. The study of morality, or ethics, is asubfield of philosophy that examines questions such as what constitutes appropriate behaviour? Thefields of corporate ethics, legal ethics, bioethics, medical ethics, engineering ethics, and computer ethicshave all seen an increase in the number of ethics centres and programmes dedicated to the study ofethics. It is becoming increasingly clear that cybercrime poses a significant risk. There are severalreasons why computer technology is considered to be one of the most essential general purposetechnologies in this day and age. In today’s day and age, it is utilised by practically all of the businesses,establishments, and people. Computer technology makes life so much quicker and more efficient, but italso exposes people to a new kind of crime known as Cybercrime, which is one of the most dangeroustypes of criminal activity. Cybercrime is a type of offence that deals with the cyber world andencompasses computer security, information security, and mobile security as well. The development ofinformation technology provides a lot of benefits to us, but it also brings a lot of issues and obstacles.Everyone is becoming increasingly interested in cybercrime as a result of the growing number ofoffences committed in the world of information technology.